(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To determine functional outcome after patellar resurfacing using bony landmarks in patients undergoing total knee replacement. Methodology: After permission from ethical committee and research department, 151 patients fulfilling the inclusion criteria from Institute Of Orthopaedics & Surgery and South City Hospital Karachi, Pakistan were included in this descriptive case series using non – probability purposive sampling technique. These patients were managed by patellar resurfacing using bony landmarks as per hospital protocols. They were followed up every 2 weeks for first two months and then monthly once after that for 6 months. During each follow-up, the patients was examined for both subjective symptoms and objective signs which was recorded and knee mobilization was employed after 3 weeks of procedure. Patients were trained for dynamic exercises (isotonic and isokinetic exercises) of the knee and were advised to follow them for compliance. Functional outcome in term of excellent, good and poor was assessed after 6 months. Results: This study included 151 patients undergoing total knee replacement, having mean ages 57.36 ± 8.01 years (range; 44 – 70 years). Of these 151 patients, 33.1 % (n = 50) were male and 66.9 % (n = 101) were female patients having mean ages 58.54 ± 5.97 years and 56.71 ± 8.81 years (p = 0.206), respectively. Rural background was noted in 33.1%(n=50) while 66.9% (n=101) were from urban localities. Mean duration of disease was 4.27 ± 2.11 years and 69.5 % (n=105) had duration more than 2.5 years. Diabetes was noted in 31.1 % (n=47), hypertension in 50.3% (n=76) and 22.5% (n=34) were obese (Mean BMI was 26.21± 2.19 kg/m2). Functional outcome was excellent in 87.4 % (n = 132) while good 12.6% (n=19). Conclusion: Patellar resurfacing using bony landmarks is safe, reliable effective procedure among patients undergoing total knee replacement as high proportion of functional outcome was excellent in our study, so our study results support the use of patellar resurfacing using bony landmarks to achieve desired outcomes to improve quality of life and physical productivity in our patients. Functional outcome was significantly associated with younger age groups, diabetes and hypertension.